The heart of a stranger : an anthology of exile literature - Naffis-Sahely, André (Pushkin, 2019)
Exile lies at the root of our earliest stories. Charting varied experiences of people forced to leave their homes from the ancient world to the present day, The Heart of a Stranger is an anthology of poetry, fiction and non-fiction that journeys through six continents, with over a hundred contributors drawn from twenty-four languages. Highlights include the wisdom of the 5th century Desert Fathers and Mothers, The Flight of the Irish Earls, Madame de Stael's thoughts on Napoleon's tyranny, Emma Goldman's travails in the wake of the First Red Scare, Ngugi wa Thiong'o's tales of European colonial settlers in Kenya and the work of the contemporary Eritrean poet Ribka Sibhatu. Edited by poet and translator Andre Naffis-Sahely, The Heart of a Stranger offers a uniquely varied look at a theme both ancient and urgently contemporary.